Retrospective study of oral lesions in the population attended at the Dental Specialty Center - Maurício Roth Volkweis; Roberta Garcia; Cassiano Adames Pacheco (Faculdade São Leopoldo Mandic, 2010)
Objectives: To identify the most prevalent stomatologic lesions in the population attended at the Dental Specialty Center of the Hospital "Nossa Senhora da Conceição", quantify the distribution by sex and age group, verify the relationship of smoking as a predisposing factor to oral cancer, determine the number of consultations at the service for each patient until discharge and quantify the number of procedures performed. Methods: The sample consisted of 435 medical records of patients who sought the Stomatology Service of the Dental Specialty Center of the Hospital Nossa Senhora da Conceição. Of these, 249 were women and 186 were men. Therefore, a retrospective study was conducted from the analysis of the clinical records of all patients attended from October 2006 to March 2008. The variables were categorized and analyzed by Pearson's Chi-square test. Results: Of the 435 patients, who sought the Stomatology service, 249 were women and 186 were men, and no statistically significant association of sex with any group of diseases was observed. The most prevalent diseases were stomatitis with 122 cases. Eighteen patients had malignant diseases (4%), 15 of them being diagnosed with squamous cell carcinoma. Of the total number of patients attended, 20.7% were referred to other professionals, 79.3% had their problems solved exclusively at the service, and in 173 cases (39.7%) biopsies were performed. Conclusion: The most prevalent lesion group was stomatitis, being 28% of the total, and the predominant groups were women and the age group over 60 years. There was a statistically significant relationship between smoking and mouth cancer.